PKPU Moratory As a Form of Proof of Failure to Pay - Ratibulava Ratibulava; Steppanus Meky Cresiawan; Muhammad Firmansyah Nasution (Budapest International Research and Critics University, 2022)
The most appropriate Debt Moratorium at this time is the Bankruptcy mechanism and PKPU, by looking at the good faith of the Debtor, then the creditor can estimate that the debtor is able to pay its obligations by postponing / moratorium on the debt as outlined in the peace plan. The idea of a bankruptcy moratorium and PKPU started from the increase in cases registered in commercial courts and other economic impacts, so it can actually be said that a moratorium is not the right solution. Reviewing the discussion of the moratorium can be done if there is uncertainty in the situation and if the moratorium is carried out it will bring goodness and order to all parties. The moratorium on bankruptcy cases and PKPU is not an effective solution, considering that the bankruptcy institution and PKPU were born from Law Number 37/2004. This means that the idea of a moratorium must go through a legislative process so that it can be in sync with Law No. 37/2004. This mechanism is not easy and will take a long time so that the idea of a moratorium is technically a law and regulation. Likewise, technically judicial, the moratorium idea is related to the limitation of the competence of the commercial court so that it is necessary to synchronize the legislative and judicial functions, if implemented it will cause many problems so that it will be more effective and efficient to revise Law No. Compared to a moratorium on bankruptcy and PKPU cases, revising the two regulations will be more effective in resolving the negative impacts that arise in connection with bankruptcy and PKPU cases in commercial courts.